) 2 1 )( 3 2 )( 3 2 (6)( + − = x x x xP 3 2 , 3 2 −

Commentaires

Transcription

) 2 1 )( 3 2 )( 3 2 (6)( + − = x x x xP 3 2 , 3 2 −
Les résultats:
1
1) P ( x) = 2( x − 2) 2 ( x + 3)( x + )
2
racines: 2,−3,−
2) P( x) = ( x + 1)( x − 2) 2
racines: − 1,2
3) P( x) = 6( x −
2
2 2 1
)( x +
)( x + )
3
3
2
racines:
1
1
1
4) P( x) = 8( x − )( x 2 + x + )( x + 3)( x 2 − 3 x + 9)
2
2
4
(
)
5) P ( x) = ( x − 2 )( x + 2 )( x 2 + 2) x 4 + 1
2
2
,−
3
3
racines: − 3,
racines:
1
2
1
2
2 ,− 2

Documents pareils